2019
DOI: 10.30969/acsa.v15i1.1024
|View full text |Cite
|
Sign up to set email alerts
|

Minicepas de Myracrodruon urundeuva submetidas a três alturas de decepa e a aplicação de Cyperus rotundus

Abstract: Myracrodruon urundeuva Allemão é uma espécie propagada geralmente com o uso de sementes. No entanto, a escassez hídrica na região semiárida pode comprometer a produção ou causar a rápida perda de vigor de suas sementes. Uma das alternativas de propagar a espécie quando há limitação de sementes é o uso da técnica de miniestaquia. O trabalho teve como objetivo avaliar minicepas de M. urundeuva de origem seminal, a partir do 2º ano de seu estabelecimento, submetidas a diferentes alturas de decepa (10, 25 e 40 cm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
2
0
0
1
Order By: Relevance
“…At 70 days, average values of 90.3%, 86.1% and 93.1% of minicutting survival were observed for sizes 5.0 cm; 8.0 cm and 11.0 cm in length, respectively. High survival values of minicuttings, as found in this research, regardless of the size of the propagules, show that the rooting environment presented favorable conditions for rooting (JUSTINO et al (2017).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…At 70 days, average values of 90.3%, 86.1% and 93.1% of minicutting survival were observed for sizes 5.0 cm; 8.0 cm and 11.0 cm in length, respectively. High survival values of minicuttings, as found in this research, regardless of the size of the propagules, show that the rooting environment presented favorable conditions for rooting (JUSTINO et al (2017).…”
Section: Resultssupporting
confidence: 68%
“…Evaluating Myracrodruon urundeuva Allemão mini-cuttings with the same lengths as in this work, Justino et al (2017) found that the treatment with mini-cuttings of 5.0 cm in length was superior to the other treatments. The authors argue that the larger the vegetative propagule, the greater the surface exposed to the environment.…”
Section: Resultssupporting
confidence: 52%
“…Dentre as espécies utilizadas para esse fim a Cyperus rotundus L., conhecida popularmente como tiririca tem se destacado por apresentar concentrações mais elevadas desse indutor. Várias pesquisas foram realizadas utilizando esta auxina natural presente na planta para indução do enraizamento em diversas espécies arbóreas (ROSSAROLLA et al, 2013;PIMENTA, et al, 2014, KOEFENDER et al, 2017SCARIOT et al, 2017;JUSTINO et al, 2019;COSTA et al, 2020;OLIVEIRA JUNIOR et al, 2020;LEITE et al, 2021).…”
Section: Introductionunclassified